PENGARUH NILAI-NILAI KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN EFIKASI DIRI TERHADAP KEMAMPUAN BERWIRAUSAHA: Studi Pada Pelaku Usaha Gen Z di Surabaya - Ainnur Iqbal Ariyanto (ECONOMOS, 2022)
The increasing number of business actors makes competition in the line of business increase. Including young entrepreneurs in Surabaya. With different family backgrounds, young entrepreneurs have high enthusiasm and confidence in the early stages of starting a business but are still not psychologically stable. These various conditions will certainly affect the motivation of an entrepreneur to develop and continue to hone his entrepreneurial skills. Known variables such as entrepreneurial values, family environment and self-efficacy are parameters in improving entrepreneurial skills. The purpose of this study was to determine the positive and significant influence of entrepreneurial values, family environment and self-efficacy on entrepreneurial abilities. The results showed that as many as 100 research samples stated that entrepreneurial values, family environment and self-efficacy partially and simultaneously influenced entrepreneurial abilities, while the contribution of three independent variables affected entrepreneurial abilities by 59.5%. To achieve maximum entrepreneurial ability, business actors need to increase understanding related to entrepreneurial values, especially on several indicators that are controlled such as creativity, risk taking, innovation, achievement orientation, ambition and independence in the sense of having the freedom of thought that gives birth to ideas, ideas and innovations. business. This is very important because not only to improve entrepreneurial skills, the family environment and self-efficacy will greatly assist business actors in running their business.